Stress Management Program in Selected Transport Companies in the Kingdom of Bahrain: it’s Influence on Job Performance - Rajan Babu, Manju (International Journal of Engineering and Technology, 2018)
Nowadays in all the business organizations people are bullying at work for achieving various targets. Because of this, people are becoming sick. Stress of course is one of the reasons for cardiac arrest. So here a study has conducted in order to assess the extent of stress on the people in terms of their health, behavior, work performance effectiveness, personal life and development and also tried to analyze the level of effectiveness of the implementation of stress management technique in the business organizations and its influence on their job performance. To gather the data, survey questionnaires and interviews were conducted. The participantâ€™s answers were analyzed by calculating weighted mean and correlation through SPSS. From the result it is clear that the respondents agree with the effect of stress on the performance level of employees in workplace and also in their daily life.Â Furthermore, the correlation conducted showed that there is no significance difference between the status and the level of effectiveness of stress management in business organizations. The managers and employees of Transport Companies in Bahrain are contended with the status of stress management program in terms of employee health, employee safety, performance management, stress relief and employee behavior. High cost of maintaining company health expenditures for stress-related disorders is one major problem faced by the transport companies related to stress management program. Anyways the management team in the co is high supportive for proper development and implementation of stress management program. Based on the analysis, the researcher has recommended that company should make provision for some good psychologists who have enough knowledge about stress handling techniques. Management staff and employees in the Company should get an ambiance for practicing stress management techniques on a daily basis and also they should be provided with good recreational facilities.Â Â